Time Metaphorization: Duality of Time as a Pursuer vis-à-vis Object of Pursuit - Waliński, Jacek T. (Research in Language, 2021)
This paper discusses the duality of metaphorical conceptualizations of time focusing in particular on time as a pursuerand time as an object of pursuit metaphors, which are based the Figure–Ground reversal of each other. Using examples taken from the British National Corpus, it argues that these metaphorical conceptualizations of time are inconsistent with each other. This inconsistency resembles the discrepancy between the moving time and moving observer metaphors, which are, in strict terms, also inconsistent with each other. Looking at such contrasts between metaphorical representations of time from a broader perspective suggests that the concept of time arises from different, both physical and socio-cultural, dimensions of human experience.